2018
DOI: 10.1111/sms.13091
|View full text |Cite
|
Sign up to set email alerts
|

Resistance band training or general exercise in multidisciplinary rehabilitation of low back pain? A randomized trial

Abstract: Multidisciplinary biopsychosocial rehabilitation has been recommended for chronic low back pain (LBP), including physical exercise. However, which exercise modality that is most advantageous in multidisciplinary biopsychosocial rehabilitation is unclear. In this study, we investigated whether multidisciplinary biopsychosocial rehabilitation could be more effective in reducing pain-related disability when general physical exercise was replaced by strength training in the form of progressive resistance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
(81 reference statements)
3
31
0
1
Order By: Relevance
“…Of all 15 trials identified, only two used the Oswestry Disability Index as their primary outcome measure. 24,25 The changes they observed in back-specific disability are similar to those we observed with a within-group decrease of between 7 and 9 points at the 12-week follow-up 24 and a within-group decrease between 2 and 5 points at the 52-week follow-up. 25 Neither of these trials found significant between-group differences, 24,25 similar to our results.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Of all 15 trials identified, only two used the Oswestry Disability Index as their primary outcome measure. 24,25 The changes they observed in back-specific disability are similar to those we observed with a within-group decrease of between 7 and 9 points at the 12-week follow-up 24 and a within-group decrease between 2 and 5 points at the 52-week follow-up. 25 Neither of these trials found significant between-group differences, 24,25 similar to our results.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, no single outcome measure has been developed and validated to measure the domain of integrating knowledge, skills, and behaviours into daily life. We identified three further trials [23][24][25] in addition to the 12 trials already included in the most recent Cochrane review 3 that compared two or more multidisciplinary rehabilitation programmes. Of all 15 trials identified, only two used the Oswestry Disability Index as their primary outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCT was carried out at an outpatient hospital back-and neck-pain clinic (hereafter termed "the clinic") at the Department of Physical Medicine and Rehabilitation, St Olavs Hospital, Trondheim, Norway. This trial has a similar design and recruitment procedure as a previous RCT in patients with low back pain, and the methods are partly overlapping (22,23). Patient characteristics were registered at baseline, while primary and secondary effect measures were obtained at baseline, week 3 and week 12.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…Performing stretching exercises (SE) can reduce discomfort and pain and also increase the range of motion 1 consequently could reduce chronic musculoskeletal pain 2 . Specialists recommend that multidisciplinary biopsychosocial rehabilitation and physical exercise are a crucial component of pain 3 Despite the fact that exercise programs have been proven to benefit people with pain [4][5] . Physical inactivity in adults is highest in the eastern Mediterranean countries as well as Iran.…”
Section: Introductionmentioning
confidence: 99%